Miscanthus Grass as a Novel Functional Fiber Source in Extruded Feline Diets - Finet, Shannon E.; Southey, Bruce R.; Rodriguez-Zas, Sandra L.; He, Fei; de Godoy, Maria R. C. (Frontiers in Veterinary Science, 2021)
Although dietary fiber is not considered an essential nutrient in a complete and balanced diet for felines, it provides a substrate for fermentation by gut microbiota, thus promoting gastrointestinal health through the production of fermentative metabolites, as well as improving laxation. The aim of this research was to evaluate the novel fiber source, miscanthus grass (Miscanthus giganteus) in comparison to traditional fiber sources, and their effects on fecal quality, apparent total tract digestibility (ATTD), fecal fermentative end-products, and microbiota of healthy adult cats. Four dietary treatments were evaluated, differing in dietary fiber source. The diets were formulated to meet or exceed the AAFCO (2018) nutritional profile for adult cats and contained either cellulose (CO), miscanthus grass fiber (MF), a blend of miscanthus fiber and tomato pomace (MF+TP), or beet pulp (BP). The study was conducted using a completely randomized design with twenty-eight neutered adult, domesticated shorthair cats (19 females and 9 males, mean age 2.2 ± 0.03 yr; mean body weight 4.6 ± 0.7 kg, mean body condition score 5.6 ± 0.6). The experimental period comprised 21 d, and a fresh and total fecal collection were performed during the last 4 d of the trial period. Daily food intake (DM basis) was similar across all groups (P > 0.05). Additionally, treatment did not affect fecal output (as-is or DM basis), fecal score, or fecal pH (P > 0.05). Cats fed BP had significantly higher total dietary fiber ATTD than all other treatments (P < 0.05), and the highest concentrations of total short-chain fatty acid, acetate, and propionate (P < 0.05), while butyrate concentrations were similar for all treatments (P > 0.05). Inclusion of dietary fibers was an effective in modulating gut microbiota. Cats fed diets containing miscanthus grass had greater α-diversity than cats fed BP. As no adverse effects on health, fecal quality, or ATTD of macronutrients were observed with the inclusion of 9% miscanthus grass fiber or fiber blend, the data suggest that miscanthus grass fiber and fiber blends are viable alternatives to the traditional dietary fiber sources used in commercial extruded feline diets, being most comparable to cellulose.